RELEVL4NSI PENGEMBANGAN CAI BIDANG PENDIDIKAN - Sunaryo Soenarto; Edy Supriyadi (LPMPP Universitas Negeri Yogyakarta, 2002)
The development of computer and multimedia technologyhas been so swift that it has led to changes in many facets ofman's life In the educational sector, the potential role of the multimediacomputer as a learning aid, source, and strategy has been ,.able to improve students' /earning motivation, interaction, andefficiency The strategy of using Computer -4ssistedInstruction (CAI) has empirically shown that CAI is able to promotelearning effectiveness.The development of the CAI program at the level of highereducational institution in the effort of sustaining the developmentof students' competence to make them competitive studentsindividually is at present the target of educational institutions'accountability in innovation and vision. The development of theCAI program is a synergic and integrated step of needs analysis,design, development, and implementation. This step should involvea group of experts, creative workers, and production staff.I11 order to implement such a project, the State University ofYogyakarta should be able to manage the visions and programsof its Learning Resource Development Unit, Computer Center, CurPnculum and Educational Techology Depmment. andElectronic EngineeIlng Department to empower Its human resourcesand equipment in ax Integrated and synergic way for thedevelopment and production of interactive multimedia hnstmction-based CAI.